2014
DOI: 10.1080/19440049.2014.905874
|View full text |Cite
|
Sign up to set email alerts
|

Silver migration from nanosilver and a commercially available zeolite filler polyethylene composites to food simulants

Abstract: Polyethylene composites containing Agion(TM) commercial silver ion filler at three different percentage fill rates (0.5, 1.0 and 2% w/w) and polyethylene composites containing laboratory produced silver nanoparticles (Agnps) at two different percentage fill rates (0.1 and 0.5% w/w) underwent migration tests according to Commission Regulation (EU) No. 10/2011. Migrated silver in the two simulants (acidified water with 3% acetic acid and distilled water) was quantified using two techniques: inductively coupled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…There have been attempts to quantify the total Ag release rates from various consumer products, including food contact materials (von Goetz et al 2013;Huang et al 2011;Hauri and Niece 2011;Song et al 2011;Bott et al 2011;Smirnova et al 2012;Echegoyen and Nerín 2013;Cushen et al 2014;Artiaga et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There have been attempts to quantify the total Ag release rates from various consumer products, including food contact materials (von Goetz et al 2013;Huang et al 2011;Hauri and Niece 2011;Song et al 2011;Bott et al 2011;Smirnova et al 2012;Echegoyen and Nerín 2013;Cushen et al 2014;Artiaga et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Composites with different nanosilver concentrations are commercially available. Cushen et al (2014) have reported 0.1–0.5% filling rate of composites analyzed for exploring silver migration into solutions. The composites usually are consumed for packaging liquid products not for dry crops like saffron.…”
Section: Discussionmentioning
confidence: 99%
“…particulate migration, was made for the subsequent exposure assessments. A more recent paper, by the same authors, compared TEM images of the silver particles prior to insertion in the matrix and after migration, which showed a significant reduction in size of the particles. These results led them to conclude that the majority of the silver migrated in the ionic form.…”
Section: Migration Other Exposure Routes and Environmental Consideramentioning
confidence: 99%